2021
DOI: 10.47144/phj.v54i3.2167
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Differences in Clinical Profile and Outcome of Primary Percutaneous Coronary Intervention in Patients With St-Segment Elevation Myocardial Infarction

Abstract: Objectives: A conflict of evidence exists regarding the gender-based differences in outcomes after primary percutaneous coronary intervention (PCI), therefore, aim of this study was to compare the clinical characteristics, angiographic findings, and outcome of primary PCI for men and women. Methodology: Data for this study was extracted from a prospectively managed primary PCI database of the National Institute of Cardiovascular Diseases (NICVD), Karachi, Pakistan. We included consecutive patients of either ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
3
2
Order By: Relevance
“…12 The increase in METs after CR was varied in some studies. [13][14][15][16] Regarding gender, this study showed that it does not influence the METs difference after CR, which contradicts previous studies reporting significant differences in METs improvement between men and women after CR following PCI or CABG. [16][17][18][19] The gender role mechanism in METs response after CR is not fully understood, but it suggests that socioeconomic and cultural factors, including disparities in health care access, variations in exercise completion, societal expectations, and lifestyle patterns, can also impact CR outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…12 The increase in METs after CR was varied in some studies. [13][14][15][16] Regarding gender, this study showed that it does not influence the METs difference after CR, which contradicts previous studies reporting significant differences in METs improvement between men and women after CR following PCI or CABG. [16][17][18][19] The gender role mechanism in METs response after CR is not fully understood, but it suggests that socioeconomic and cultural factors, including disparities in health care access, variations in exercise completion, societal expectations, and lifestyle patterns, can also impact CR outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…In CR outcomes, both genders have positive results as they both have an increased post-CR METs response 12. The increase in METs after CR was varied in some studies 13-16. Regarding gender, this study showed that it does not influence the METs difference after CR, which contradicts previous studies reporting significant differences in METs improvement between men and women after CR following PCI or CABG 16-19.…”
Section: Discussioncontrasting
confidence: 86%
“…14,16 A distinctive role of gender has been well reported in the literature, it is a common observation that premature CVD or CVD event at young ages is relatively lesser common among females, an average difference of 10 years has been reported in the age of male and female patients at the time of occurrence of event. [17][18][19] Comparatively, female patients were observed to have higher prevalence of conventional CVD risk factors such as hypertensive, diabetic, and obese, frequent late presentation after symptom onset, and higher angiographic finding of three vessel disease. 16,17 All of these factors have contributed to the prognostic role of female gender with an increased risk of adverse outcomes after coronary intervention.…”
Section: Discussionmentioning
confidence: 97%
“…[17][18][19] Comparatively, female patients were observed to have higher prevalence of conventional CVD risk factors such as hypertensive, diabetic, and obese, frequent late presentation after symptom onset, and higher angiographic finding of three vessel disease. 16,17 All of these factors have contributed to the prognostic role of female gender with an increased risk of adverse outcomes after coronary intervention. [16][17][18][19][20][21][22] Converse to the local norms, an equal proportion of smoking among females as male counterparts in this particular population can be attributed to the cultural acceptability of domestic use of huqqa in this population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation